Gravity for FDI - Jörn Kleinert; Farid Toubal (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2007)
Gravity equations explaining foreign affiliates' sales are ad hoc and hence, estimated coeffcients are hard to interpret. We therefore provide the theoretical underpinnings of the gravity equation applied to the analysis of sales of foreign affiliates of multinational firms. We argue that the success of the gravity equation results from the fact that it can be derived from various theoretical models. We illustrate this point by deriving a gravity equation from three different models of multinational firms. Using data on real affiliate sales, we show how this derived gravity equation can nevertheless be used to discriminate between the different theoretical models. - gravity equation ; multinational firms ; heterogeneity
urn:nbn:de:bsz:21-opus-30718
Keywords: F23; F12; C21; 330; Direktinvestition; Multinationales Unternehmen; Gravitationsmodell; Faktorproportionentheorem; Allgemeines Gleichgewicht; Theorie